CLINICAL UTILITY OF CAT SCORE IN PATIENTS WITH COPD EXACERBATION AND STABLE DISEASE AND ITS CORRELATION WITH PULMONARY FUNCTION TESTS: AN OBSERVATIONAL PROSPECTIVE STUDY - Dr. R. J. Khyalappa; Dr. S. M. Thanekar (Medico Research Chronicles)
Background: Burden of COPD is on rising and is a common cause of hospitalization and mortality. Presently Pulmonary Function Tests (PFT) is the common diagnostic tool as well as tool for assessing severity of COPD. However, PFT are not routinely available at Primary Health Centre. Present research aims to study clinical utility of CAT score for assessing COPD severity so that it can be used where PFT is unavailable. Materials & Methods: Aim of this study was to assess the correlation between CAT score and PFT parameters in stable COPD and its exacerbation. 50 patients from both form of the disease were included in the study. CAT score was noted & PFT was performed for stable COPD patients during their routine OPD visit and at day1 & day5 for those requiring hospitalization for COPD exacerbation. Observations: We found significant difference between each study group (Stable COPD patients, Day1 of COPD exacerbation and Day5 of COPD exacerbation) in all three parameters i.e. CAT score, FEV1 (%pred) and FVC (%pred) (p<0.05). CAT score also correlates with the change in FEV1 (%pred) and FVC (%pred) during a COPD exacerbation. Also, there was negative correlation between FEV1 (%pred) and FVC (%pred) with CAT score in stable COPD patients. Conclusion: CAT scores correlates with PFT parameters in stable COPD as well as acute exacerbation of COPD. Outcome: CAT score can be utilized to assess the severity of COPD especially in resource limited setups where there is no facility for Pulmonary Function Testing and also it is cost effective.